NNT‐induced tumor cell "slimming" reverses the pro‐carcinogenesis effect of HIF2a in tumors. Issue 1 (12th January 2021) - Xiong, Zhiyong; Xiong, Wei; Xiao, Wen; Yuan, Changfei; Shi, Jian; Huang, Yu; Wang, Cheng; Meng, Xiangui; Chen, Zhixian; Yang, Hongmei; Chen, Ke; Zhang, Xiaoping
Abstract: Background: HIF2a and lipid accumulation play key roles in the progression of clear cell renal cell carcinoma (ccRCC). Tumor cell "slimming" is a new concept in which tumor cells with abnormal lipids efficiently consume lipids to inhibit tumor progression without producing additional ATP. However, their respective regulatory mechanisms are still unclear. The purpose of this study is uncovering the links between these three key elements of ccRCC to elucidate new mechanisms of ccRCC metabolic abnormalities and providing a basis for new drug development for ccRCC. Methods: Bioinformatics screening and analyses were performed in ccRCC according to TCGA‐KIRC database. qRT‐PCR, luciferase reporter assay, western blot, chromatin immunoprecipitation (ChIP) assays, and other biological methods were used to explore and verify related pathways. Various cell line models and animal models were used to perform related functional experiments. Results: Screening based on sequencing data after HIF2a knockdown and three independent mitochondrial metabolism‐related gene sets showed that nicotinamide nucleotide transhydrogenase (NNT) was a mediator between HIF2a and tumor cells "slimming." Further research showed that NNT had significant prognostic predictive value and was downregulated in ccRCC. It is regulated by HIF2a and can significantly activate lipid browning‐mediated tumor cell "slimming." Mechanistic investigations indicated that HIF2a enhanced the expression of miR‐455‐5p via binding to HIF2a‐related response elements in the miR‐455‐5p promoter, which suppresses NNT expression by binding to its 3′ untranslated region. Conclusions: Our study revealed a novel mechanism by which HIF2a decreased NNT level through a microRNA that suppressed tumor cell "slimming, " resulting in the progression of ccRCC. This mechanism provides a fresh perspective of lipid accumulation in ccRCC and may help target novel strategies for the treatment of tumors with abnormal lipid metabolism. Abstract : A model could be suggested in which HIF2a increases miR‐455‐5p expression by binding to HIF2a response elements in the miR‐455‐5p promoter, which suppresses NNT expression by binding to its 3'UTR. Meanwhile, NNT promotes lipid browning to consume lipids, resulting in the suppression of ccRCC progression.